A Metastatic Intrahepatic Cholangiocarcinoma With HPCs Features: Report of a Case - Fu, Qiang; Liu, Pan; Jin, Shangkun; Zhang, Xu; Liu, Chuanjiang; Hu, Mingxing; Wang, Yuzhu; Zhang, Hongwei; Qin, Tao (Frontiers in Oncology, 2022)
Intrahepatic cholangiocarcinoma (ICC) is a highly lethal hepatobiliary neoplasm, which originates from the bile ducts proximal to the second-order division. ICC can be anatomically divided into two subtypes: the large duct type (mucin-production ICC, muc-ICC) and the small duct type (mixed-ICC) origins from hepatic progenitor cells (HPCs). The immunoreactivity of S100P and neural cell adhesion molecule (NCAM) are useful biomarkers to distinguish the two subtypes. In this study, we report a difficult-to-diagnose case of metastatic retroperitoneal tumor of occult hepatolithiasis-associated ICC. Besides, this case was both positive for S100P and NCAM, considered as a rare muc-ICC with the HPCs features. Tumor whole exome sequencing detection results by Genetron (China) revealed that there were 41 gene mutations in this patient. The SMAD4-p.His530ThrfsTer47 and KRAS-p.Gly12Val mutation might promote the occurrence and distant metastasis of the tumor.